Pyoderma gangrenosum resembling Paget’s disease - Maj, Joanna; Maciąg, Henryk; Barancewicz-Łosek, Maria; Plomer-Niezgoda, Ewa (Contemporary Oncology/Współczesna Onkologia, 2006)
We present a 72- year-old woman with an ulceration of her left breast in the course of pyoderma gangrenosum (PG). Histiologically, the skin biopsy was interpreted as Paget’s disease and the proper treatment was introduced for 9 months without success. The revaluation of the skin biopsy sample in addition to specific clinical course (rapid ulceration of the inflammatory lesion and violent recurrence after the first surgery) allowed us to establish the diagnosis of PG. The therapy comprised oral prednisolone at dose of 50 mg daily and disulone in a dose of 100 mg/d. After 3 weeks of treatment almost complete clearance of the lesion was achieved. The diagnosis of PG is difficult and based mainly on the clinical course and manifestation. Histopathology is unspecific. The diagnosis and treatment of PG is an interdisciplinary problem because of the variety of systemic disorders associated with PG e.g.: inflammatory bowel diseases, rheumatoid arthritis, myeloid leukaemia, monoclonal gammapathy, myelofibrosis, hepatopathies.